2020
DOI: 10.1002/eat.23365
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating,self‐esteem, and depression symptoms in Iranian adolescents and young adults: A network analysis

Abstract: Objective The network theory of psychopathology examines networks of interconnections across symptoms. Several network studies of disordered eating have identified central and bridge symptoms in Western samples, yet network models of disordered eating have not been tested in non‐Western samples. The current study tested a network model of disordered eating in Iranian adolescents and college students, as well as models of co‐occurring depression and self‐esteem. Method Participants were Iranian college students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
63
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 85 publications
12
63
2
Order By: Relevance
“…They found that approximately 7% screened positive for an ED, and that urban residence and higher levels of education were associated with greater risk. Meanwhile, in Iran, Sahlan et al (2021a) found that approximately 12% of adolescent boys and 13% of adolescent girls met the operational definition of a probable ED case. Perhaps most alarmingly, Chua, Fitzsimmons‐Craft, Austin, Wilfley, and Taylor (2021) studied the estimated prevalence of EDs in Singapore, reporting that while approximately 6% screened positive for a clinical ED, a further 37% screened positive for other specified feeding or eating disorder, and another 19% were at high risk for developing an ED.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…They found that approximately 7% screened positive for an ED, and that urban residence and higher levels of education were associated with greater risk. Meanwhile, in Iran, Sahlan et al (2021a) found that approximately 12% of adolescent boys and 13% of adolescent girls met the operational definition of a probable ED case. Perhaps most alarmingly, Chua, Fitzsimmons‐Craft, Austin, Wilfley, and Taylor (2021) studied the estimated prevalence of EDs in Singapore, reporting that while approximately 6% screened positive for a clinical ED, a further 37% screened positive for other specified feeding or eating disorder, and another 19% were at high risk for developing an ED.…”
Section: Prevalencementioning
confidence: 99%
“…This study showed that addiction‐like eating in young Asian adults was correlated with negative mood, as reported in non‐Asian samples, and also with personality traits linked to other forms of behavioral addictions. Sahlan, Williams, et al (2021a) tested a network model of disordered eating in Iranian adolescents and college students, as well as models of co‐occurring depression and self‐esteem. Within this group, desire to lose weight was the most central node in the network, consistent with sociocultural theories of ED development and transdiagnostic models of EDs.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Cultivation of self-esteem in early childhood reinforces positive values that can help children optimally cope with dynamic life situations [3,[9][10][11][12][13], and is related to several markers of wellbeing, such as happiness, life satisfaction, self-confidence in social situations, sociability, and optimism [14,15]. However, low self-esteem among children is associated with negative thoughts, avoidance of new experiences, difficulty in managing conflicts [1,16], poor physical and mental health later in life [17], depression [18,19], loneliness [20], suicidal thoughts [21], suicide attempts [22], eating disorders [23,24], anxiety [25], behavioral problems [26], drug and alcohol addictions [27], as well as criminal and anti-social behavior [27]. It is not surprising, then, that high self-esteem has been identified as a buffer against the onset of mental illness in childhood [28] and it functions as a mechanism for reducing stress [29] even when they face extremely stressful situations [25,30].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies on network analysis of psychopathology in young adulthood. However, most studies were conducted on groups in the general population, such as college students 16 , or on the general population focusing on eating disorders 17 . In our previous study 18 , using the same sample, the effect of verbal abuse on psychiatric symptoms was mainly studied.…”
Section: Introductionmentioning
confidence: 99%